Developing crown shape model considering a novel competition index — a case for Korean pine plantation in Northeast China - Sun, Yunxia; Feng, Jian; Chen, Dongsheng; Gao, Huilin; Zou, Hongtao (Canadian journal of forest research, 2022)
Effect of neighbor tree competition on crown shape of Korean pine plantation in Northeast China was studied. A total of 48 trees aged 7–58 years were felled, and all living branches were measured. A novel neighbor competition index that considered the overlap length between subject tree and neighbor tree crowns was created and incorporated into crown shape model. The effects of neighboring competition on crown shape, largest crown radius, and inflection point were analyzed. A dummy variable approach was used to detect crown asymmetry. The crown length index (CLI) of the subject tree was selected as the best neighbor competition index, and the mean square error reduction compared with that of the basic model was 2.0% after incorporating CLI. Crown radius displayed differences in the four cardinal directions and followed the order north > west > south > east. The crown radius in four directions for different ages decreased with increasing CLI and the difference increased with increasing tree age. The competition index, which considers horizontal and vertical competition effects, can significantly improve the performance of crown shape model. Both of inflection point and largest crown radius increased with increasing of CLI; however, the Pearson correlation coefficient was not significant ( P > 0.05).